PARASITOIDS OF SYNANTHROPIC FLIES COLLECTED IN BOVINE KIDNEY IN ITUMBIARA, STATE OF GOIÁS, BRAZIL - Marchiori, Carlos Henrique; Pereira, Luiz Alex; Filho, Otacilio Moreira Silva; Ribeiro, Lalyne Cristhine Silva; Borges, Vanessa Rodrigues (Revista de Patologia Tropical / Journal of Tropical Pathology, 2011)
Species of parasitoids associated with synanthropic flies were collected in bovine kidney, inItumbiara, State of Goiás, from March 2001 to March 2002. The pupae were obtaíned by the flotation method. They were individualiy placed in gelatin capsules until the adult flies ortheir parasitoids emerge. The overall prevalence of parasitism was 23.9%. The parasitoids Brachymería podagrica, Nasonia vitripennis, Pachycrepoideus vindemiae, Paraganaspis egeria and Spalangia endius presented a parasitism prevalence of 7.0%, 12.4%, 3.5%, 0.5% and 0.6%, respectively.